INJURY SOYBEAN SEEDS, ITS TYPES AND CAUSES - Погоріла, Л. Г. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
Researches were conducted during 2013-2015. In the article it is suggested to consider the results of researches on a degree and character of injuring of seeds of soy of different groups of ripeness depending on a fertilizer and humidity of seeds in a time of harvest. It is set researches, that optimum collective humidity for the seeds of soy which the least injuring is at the level of 12-14%. At the increase of this index to 15-16% the amount of micro injured seeds, decline of humidity increased to 10-11% cause to macro injuring. The influence of injuring of seed on energy of germination and laboratory similarity was invistagated. It was discovered that, macro injured seeds had on the average on 12,3% lower energy of germination and on 11,4% laboratory similarity relatively to whole seeds. The laboratory similarity of micro injured seeds not substantially differs from whole, on the average on 5,8%.